Jack at the zoo - Barnett, Mac; Pizzoli, Greg (New York : Viking, 2020)
Jack, Rex, and the Lady visit the zoo. But when Jack gets hungry, he sneaks into a koala's cage to steal some snacks. In a case of mistaken identity, the Lady takes the koala home and leaves Jack stuck in the cage. How will Jack escape, and will the Lady and Rex be happier with the new Jack?
K-3
Keywords: Zoos -- Juvenile fiction; Dogs -- Juvenile fiction; Rabbits -- Juvenile fiction; Zoos -- Fiction; Dogs -- Fiction; Rabbits -- Fiction; Readers (Elementary)